Extended fatigue life of a catalyst free self‐healing acrylic bone cement using microencapsulated 2‐octyl cyanoacrylate. Issue 2 (14th May 2014) - Brochu, Alice B. W.; Matthys, Oriane B.; Craig, Stephen L.; Reichert, William M.
Abstract The tissue adhesive 2‐octyl cyanoacrylate (OCA) was encapsulated in polyurethane microshells and incorporated into bone cement to form a catalyst free, self‐healing bone cement comprised of all clinically approved components. The bending strength, modulus, and fatigue lifetime were investigated in accordance with ASTM and ISO standards for the testing of PMMA bone cement. The bending strength of bone cement specimens decreased with increasing wt % capsules content for capsules without or with OCA, with specimens of <5 wt % capsule content showing minimal effect. In contrast, bone cement bending modulus was insensitive to capsule content. Load controlled fatigue testing was performed in air at room temperature on capsule free bone cement (0 wt %), bone cement with 5 wt % OCA‐free capsules (5 wt % No OCA), and 5 wt % OCA‐containing capsules (5 wt % OCA). Specimens were tested at a frequency of 5 Hz at maximum stresses of 90%, 80%, 70%, and 50% of each specimen's bending strength until failure. The 5 wt % OCA exhibited significant self‐healing at 70% and 50% of its reference strength (p < 0.05). Fatigue testing of all three specimen types in air at 22 MPa (50% of reference strength of the 5 wt % OCA specimens) showed that the cycles to failure of OCA‐containing specimens was increased by two‐fold compared with the OCA‐free and capsule‐free specimens. This study represents the first demonstration of dynamic, catalyst free self‐healing in a biomaterial formulation. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 305–312, 2015.